Assessment of the Potentials of Water Hyacinth (Eichhornia crassipes) as Raw Material for Biofertilizer - , M. O. Ikuesan; , V. O. Oyetayo; , O. P. Ayelari (Archives of Current Research International, 2023)
This research investigated the potentials of water hyacinth as raw material for biofertilizers. Water hyacinth was collected from Alape River in Ilaje Local Government Area of Ondo State and processed for microbiological, proximate and physicochemical analyses by standard methods. Results revealed that the total heterotrophic bacterial and fungal populations were 5.0 x 107 (CFU/g) and 3.5 x 105 (CFU/g) and 3.6 x 102 SFU/g and 3.0 x 102 (SFU/g) for root and leaf parts respectively. The population of phosphate solubilizing bacteria, Azospirillum spp., Azotobacter spp. and Rhizobium spp. were 3.5 x 104 - 1.3 x 106 CFU/g, 1.4 x 103- 2.6 x 104 (CFU/g), 3.4 x 103 – 1.7 x 104 (CFU/g) and 1.2 x 103 – 1.1 x 104 (CFU/g) respectively. 16S rRNA gene sequencing revealed the presence of Enterobacter cloacae (LT 221670.1 -53%) and Bacillus safensis (AB711138.1 -99%), Pseudomonas mendocina (LN 881702.1 – 99%) and Aeromonas veroni (LC 487867.1 – 97%) from the root and leaf respectively. Aspergillus spp., Fusarium sp., Rhizopus sp., Trichoderma sp. Cladosporium sp. were among the fungi from the water weed parts. The proximate, nutrient and heavy metal constituents of water hyacinth vary among the leaf, stem and root. The proximate values for moisture (65.45%), protein (12.18%) and carbohydrate (5.30%) were highest in the leaf part compared to the stem and roots. Also, the highest values of ash (18.48%), fat (3.84%) and crude fibre (12.50%) were obtained in the plant root relative to leaf and stem. Apart from magnesium and phosphorous, mineral elements such as sodium, calcium and potassium were more abundant in the leaf. Among the heavy metal, Lead, Cadmium, Nickel, Arsenic and Cobalt had undetectable values for all parts. This study concludes that the presence of microbial biofertilizer and micro and macro nutrients on water hyacinth suggests its potential as raw material for biofertilizer and can be used to promote plant growth without negative consequences.